2002
DOI: 10.1159/000068322
|View full text |Cite
|
Sign up to set email alerts
|

Role and Mechanisms of Interleukin-1 in the Modulation of Neurotoxicity

Abstract: Objective: Recent studies on cerebral ischemia in the rat have demonstrated that administration of interleukin-1 receptor antagonist (IL-1ra) markedly reduces the volumes of infarcts which are associated with N-methyl-D-aspartate (NMDA)-mediated neurotoxicity. These observations suggested that endogenous interleukin-1 (IL-1) may be involved in the mediation of excitotoxic neuronal injury following ischemia. Method: In the present studies, we examined the role of interleukin-1β (IL-1β) in NMDA-related and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 45 publications
2
33
0
1
Order By: Relevance
“…It is to be noted that RGCs were the target of these cytokines as they vigorously expressed TNF receptor 1 (TNF-R1) and IL receptor 1 (IL-1R1). TNF-α has been shown to mediate RGC death by binding with its receptor TNF-R1 in experimental elevation of intraocular pressure and in ocular conditions such as retinal ischemia, optic nerve crush and glaucoma [78][79][80] RGC apoptosis occurs through this binding as a result of activation of caspase signaling pathways, mitochondrial dysfunction and oxidative damage [81].…”
Section: Hypoxia and Microglial Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted that RGCs were the target of these cytokines as they vigorously expressed TNF receptor 1 (TNF-R1) and IL receptor 1 (IL-1R1). TNF-α has been shown to mediate RGC death by binding with its receptor TNF-R1 in experimental elevation of intraocular pressure and in ocular conditions such as retinal ischemia, optic nerve crush and glaucoma [78][79][80] RGC apoptosis occurs through this binding as a result of activation of caspase signaling pathways, mitochondrial dysfunction and oxidative damage [81].…”
Section: Hypoxia and Microglial Activationmentioning
confidence: 99%
“…Our recent investigations have shown that increased release of IL-1β by retinal microglia and enhanced expression of IL-R1 on RGCs occurred concurrently in the retina of hypoxic neonatal rats. IL-1β can damage the RGCs by binding to its receptor IL-R1 and initiating mechanisms such as excitotoxicity and increased iNOS production through IL-R1 signalling [80].…”
Section: Hypoxia and Microglial Activationmentioning
confidence: 99%
“…It seems that IL-1β is neurotoxic only at high concentrations and after relatively long exposure [3]. Several mechanism by which IL-1 may induce neuronal death have been proposed including the involvement of glia [59] and the regulation of NMDA receptor [39,73].Neurotrophins, such as BDNF, are important modulators for neuronal survival and functions. BDNF, a major trophic factor in the CNS, is critical for the development and survival of certain neuronal populations.…”
mentioning
confidence: 99%
“…While IL-1β can cause neuronal toxicity in vivo after CNS damage, the cytokine is not directly neurotoxic to neurons in culture, but exacerbates neuronal damage by other agents [58,69]. For example, IL-1β increased excitotoxicity in vitro [39,73] and in vivo [26]. IL-1β induced neurotoxicity in vitro has been recently shown to be mediated by glia and requires free radical release and caspase activation [69].…”
mentioning
confidence: 99%
“…(18,20,58). The inflammatory process of HAD potentiates glutamate excitotoxicity through multiple factors including PAF, TNF-α, IL-1β, and various HIV proteins (59)(60)(61)(62)(63)(64)(65)(66). Glutamate excitotoxicity may be the common pathway to cognitive dysfunction (67).…”
Section: Macrophage Driven Pathogenesismentioning
confidence: 99%